Two Bronze Age Burials - Stevenson, Robert B K (Proceedings of the Society of Antiquaries of Scotland, 1939)
A stone built cist containing a cinerary urn with the cremated remains of an adult was discovered at Outerston Hill, Midlothian. Pyre debris, including a burnt worked flint flake and large sherds of a smashed and burnt second pottery vessel were also present. A second stone cist at West Pinkerton, Broxburn, East Lothian contained two adult male skeletons and a Beaker vessel. The earlier skeleton had apparently been disturbed during the burial of the second. The method of manufacture of prehistoric vessels is discussed.